Grade II Hypertension in a 59-Year-Old Woman: A Case Report - Dr. dr. Maria Selvester Thadeus, M. Biomed, Sp.KKLP, Subsp. FOMC; dr. Hikmah Mukhtamiroh, M.MedEd, Sp.KKLP, Subsp. COPC; Audya, Safira Diva; Salsabila Nanda Maharani; Kusuma Jasmine Vicky Sutrisno; Muhammad Pandji Raihan; Nuur Nazhira (Jurnal Ilmu Kedokteran Keluarga, 2026)
This case report describes a 59-year-old woman diagnosed with Grade II hypertension who presented with intermittent headaches. Risk factors included high sodium intake, stress, overweight status, and a significant family history of hypertension and diabetes mellitus. Physical examination revealed blood pressure of 160/100 mmHg without signs of target organ damage. Electrocardiogram and chest radiography results were within normal limits. The diagnosis was established based on repeated elevated blood pressure measurements. The patient received amlodipine and lifestyle modification counseling. Follow-up demonstrated gradual improvement with blood pressure decreasing to 125/85 mmHg. This case highlights the importance of addressing modifiable risk factors and ensuring treatment adherence in hypertensive patients.